A Bibliometric Analysis of the Innate Immune DNA Sensing cGAS-STING Pathway from 2013 to 2021 - Shi, Xuan; Wang, Sheng; Wu, Yutong; Li, Quanfu; Zhang, Tong; Min, Keting; Feng, Di; Liu, Meiyun; Wei, Juan; Zhu, Lina; Mo, Wei; Xiao, Zhuoran; et al. (Frontiers in Immunology, 2022)
Background and aims: Cyclic guanosine monophosphate (GMP)-adenosine monophosphate (AMP) (cGAMP) synthase (cGAS) and stimulator of interferon genes (STING) are key components of the innate immune system. This study aims to evaluate the research of cGAS-STING pathway and predict the hotspots and developing trends in this field using bibliometric analysis. Methods: We retrieved publications from Science Citation Index Expanded (SCI-expanded) of Web of Science Core Collection (WoSCC) in 1975-2021 on 16 March 2022. We examined the retrieved data by bibliometrix package in R software, VOSviewer and CiteSpace were used for visualizing the trends and hotspots of research on the cGAS-STING pathway. Results: We identified 1047 original articles and reviews on the cGAS-STING pathway published between 1975 and 2021. Before 2016, the publication trend is increasing steadily, but there was a significant increase after 2016. The United States of America (USA) produced the highest number of papers (Np) and took the highest number of citations (Nc), followed by China and Germany. The University of Texas System and Frontiers in Immunology were the most prolific affiliation and journal respectively. In addition, collaboration network analysis showed that there were tight collaborations between the USA, China and some European countries, so the top 10 affiliations are all from these countries and regions. The paper published by Sun LJ in 2013 reached the highest local citation score (LCS). Keywords co-occurrence and co-citation cluster analysis revealed that inflammation, senescence, and tumor were popular terms related to the cGAS-STING pathway recently. Keywords burst detection suggested that STING-dependent innate immunity and NF-κB-dependent broad antiviral response were newly-emerged hotspots in this area. Conclusions: This bibliometric analysis showed that publications related to the cGAS-STING pathway tend to increase continuously. The research focus has shifted from the mechanism how cGAS senses dsDNA and cGAMP binds to STING to the roles of the cGAS-STING pathway in different pathological state.